Factors obstructing the application of student-centered education at schools in Azerbaijan - Anar Khalafov (Association for Scientific Computing Electrical and Engineering(ASCEE), 2021)
Involvement of children with special educational needs in inclusive education at schools of general education in the Republic of Azerbaijan is one of the priority issues of the state. Many reforms in the education system, particularly at schools, need to be carried out to promote inclusive education. This research emphasizes the importance of implementing the student-centered education approach in the general education system to make schools inclusive in the country. As a ground for this, the article, having cited from scientific papers of different researchers, points out that, for example, a student-centered education allows a school to meet the different needs of students and take the specifics of each student into consideration. The level of progress of student-centered learning was assessed in the conducted research through studying teachers’ instructional methods at schools operating in the education system of Azerbaijan. As a result of the survey and focus group discussions conducted with teachers within this research, it was revealed that although teachers understand the positive impact of a student’s learning through student-centered methods, in most classes, they continue teaching lessons in a teacher-centered style due to several school or out-of-school factors. The result is that teacher-centered classes still being conducted at schools are not only the incompetency of teachers, but as a result, it is not possible to achieve the development of student-centered learning by improving only teachers’ skills. Many factors obstruct the change from teacher-centered learning to student-centered learning in the classroom. The identification of school culture and the classification of culture-forming factors are also discussed in this research.